Long-term Outcomes After Anterior Cruciate Ligament Reconstruction in Patients 60 Years and Older. Issue 12 (10th December 2014) - Baker, Champ L.; Jones, Jaclyn C.; Zhang, Jeff
Background: Studies evaluating the benefit of surgical reconstruction of the anterior cruciate ligament (ACL) in middle-aged patients have shown promising results, but study populations were limited primarily to patients who were 40 to 60 years old. Some authors have suggested that surgery may benefit these older patients. Hypothesis: Patients aged ≥60 years with functional instability after ACL injury would benefit from ACL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: Medical records from 1984 through 2010 were searched for patients aged ≥60 years who had undergone primary arthroscopic ACL reconstruction at a single institution. Fifteen patients (15 knees) were identified as meeting the above criteria. All patients were contacted for a telephone interview, and they completed Short Form–36 and modified Cincinnati Knee Score forms. One patient was deceased, and 1 had undergone revision to total knee arthroplasty. Among the remaining 13 patients, the mean age at surgery was 63.5 years (range, 60-73 years), and the mean patient age at the time of follow-up was 73 years (range, 65-85 years). Preoperative radiographs showed no obvious evidence of arthritis in 10 (77%) of the 13 patients; small osteophytes without loss of joint space were seen in 3 (23%) patients. The mean length of follow up was 115.7 months (range, 53-193 months). Results: At their last clinic visits, all 13 patients had regained full range of motion and returned to sports or exercise, such as tennis, golf, gym exercise, and yoga. Twelve patients reported no joint laxity. Conclusion: Patients aged ≥60 years with symptomatic instability from ACL injury can have good to excellent subjective outcomes with surgical reconstruction. Clinical Relevance: Physicians who treat active patients older than 60 years should not exclude ACL reconstruction based on the patient's age alone.